2018
DOI: 10.1080/02134748.2018.1482054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between organizational socialization and attitudes and behaviours in volunteers: the importance of organizational justice / Relación entre la socialización organizacional y las actitudes y conductas en el voluntariado: la importancia de la justicia organizacional

Abstract: This study explores the influences of organizational socialization on the intention to stay and innovative behaviours using a two-time design with a sample (N = 308) of volunteers who provide advice and guidance. Furthermore, it analyses the mediating role of perceptions of organizational justice on the relationships between socialization and results. Our findings support the proposed hypotheses; that is, they showed that the higher the organizational socialization, the higher the intention to stay and the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Orientation training is a process of onboarding initiatives as it helps new employees to integrate in the workplace. This first formal interaction with the employer and co‐workers develops a long‐lasting positive impression in the employee's mind and consequently motivates them to feel they are part of the organization (Aranda et al., 2018; Malik & Manroop, 2017). New employees in any organization typically expect support from their new employer in understanding their co‐workers, the work environment, the details of their assigned work, and organizational policies and practices (Bauer et al., 2007; Tang et al., 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Orientation training is a process of onboarding initiatives as it helps new employees to integrate in the workplace. This first formal interaction with the employer and co‐workers develops a long‐lasting positive impression in the employee's mind and consequently motivates them to feel they are part of the organization (Aranda et al., 2018; Malik & Manroop, 2017). New employees in any organization typically expect support from their new employer in understanding their co‐workers, the work environment, the details of their assigned work, and organizational policies and practices (Bauer et al., 2007; Tang et al., 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Researchers found that orientation programs provide employees with not only the onboarding information, but also new skills to perform the job and progress in their career (Benzinger, 2016). Ideally, newcomers should know what types of goals they should envision to fit in the new organization and how they can distinguish themselves from other employees (Aranda et al., 2018; Oh, 2018). For newcomers, orientation training appears particularly attractive since it provides them with the required skills to cope with emotions and problems, thus enabling new hires to successfully address problematic situations, recuperate from difficulties, and avoid losing career momentum (Homklin et al., 2014; Saks & Gruman, 2011).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%